42 SIROLIMUS IN HEART TRANSPLANTATION: A STRATEGY TO IMPROVE RENAL FUNCTION AND REDUCE THE RISK OF RENAL FAILURE. (10th December 2015) - Banchs, H. L.; Gonzalez, V.; Altieri, P.; Díaz, E.; Lopez, F.; Cancel, Gonzalez I.; Quintana, C.
Abstract : Introduction: The predominant cause of chronic renal disease after heart transplantation is the long-term use of calcineurin inhibitors (CI), either cyclosporine or tacrolimus. Sirolimus (S) has been administered successfully in the management of this complication in other solid organ recipients. We report our experience with S administered with low doses of CI or as primary therapy in combination with steroids and mycophenolate mofetil (MM) in heart transplant recipients who developed renal insufficiency (RI) after transplantation. Methods: Fifty four (54) patients have received a heart transplant since June 1999. The initial immunosuppressive regimen consisted of MM, steroids, and a CI (50 cyclosporine and 2 tacrolimus). Renal function was monitored closely with creatinine clearance (CC) determination each 3-6 months. If CC decreased below 49 mL/min per 1.73 kg per m<, the CI dosage was reduced to the minimal dose to control rejection and CC was reexamined. If renal function remained unchanged, S was started, MM discontinued and CI dose reduced in 50% (Group I). After this approach, if CC continued < 49 mL/min CI was discontinued, MM restarted and S was continued, (Group II). Results: Among 54 patients, 41 males, 13 females, mean age 47 years, 20 (37%) have diabetes mellitus (DM) and 34 (63%) hypertension. None had acute perioperative renal failure or hepatitis C, and all were receiving either an ACE inhibitor or an ARB agent. In 20 patients, S was introduced in its immunosuppressive regime to manage RI (CC < 49 mL/min). Ten required S, low dose CI, plus prednisone (Group I); and 10 S, MM, plus prednisone (Group II), at a mean time of 22 months post transplantation. The average CC increased from 38.6 mL/min to 63.5 mL/min (p < .05) in Group I, and from 38.4 mL/min to 67.4 mL/min (p < .5) in Group II after S administration. No significant change in left ventricular ejection fraction or in episodes of rejection was observed since one year before and one year after S. None of our patients have required renal dialysis. Conclusions: Our patients have a high incidence of DM, and post transplant renal insufficiency with CC < 49 mL/min, in 37% and 38% respectively. S has offered a flexible opportunity to manage this complication. Either in combination with a CI at low doses (50% dose reduction) or as a substitution therapy for the CI, we have observed a significant improvement in renal function with S without graft function deterioration or increase in rejection.